OVERVIEW OF PERSISTENCE DURING ONLINE LEARNING ON NURSING STUDENTS - Mardhiyah, Ai; Yosep, Iyus; Mediani, Henny Suzana; Rakhmawati, Windy; Hendrawati, Sri (Journal of Nursing Culture and Technology, 2024)
Background: Persistence is a key factor in determining the academic success of nursing students. The impact of persistence on students is improved academic performance, development of study skills, professional readiness, mental well-being, and engagement in academic and extracurricular activities. Nursing students' perceptions and practices of persistence are important to understand in the context of higher education. Objectives: This study aims to describe the level of persistence in Padjadjaran University Nursing students. Methods: The research method used is quantitative using the Self-Regulated Online Learning Questionnaire (SOL-Q) which consists of 5 items. The sampling technique in this study used purposive sampling. The number of samples was 100 padjadjaran university nursing students. Results: The results showed that more than half of nursing students at Padjadjaran University had low persistence, which could affect their academic performance. This can be seen from 59 respondents or as many as 59% of students showed low persistence. This findings highlights the importance of developing learning strategies that can improve the persistence of nursing students. Conclusion: In the context of nursing education, there is a need for greater efforts to improve student persistence, especially in developing their persistence, in order to improve the quality of education and their readiness for future nursing practice.